The relationship between depression and ischemic heart diseases and its risk factors among patients referred to the specialized clinic in Saqqez - Rezaie, Jahangir; Reshadi, Haleh; Salari, Nader; Sharifi saqqzie, parshang; Babazadeh, Tohid; Mahmoodi, Hasan (Advances in Nursing & Midwifery, 2017)
Abstract Background and Aim: Depression is a common disease among patients with cardiovascular disease. Depression can be related to ischemic cardiovascular risk factors such as lack of physical activity, smoking, alcohol abuse, hypertension, diabetes, and hyperlipidemia. The purpose of this study was to determine the between depression and ischemic cardiovascular disease and its risk factors. Materials and Methods: This was a descriptive study. The subjects were 200 patients with ischemic and non-ischemic heart disease in two groups. The instruments consisted of three sections: the demographic characteristics, heart diseases risk factor's assessment scale and beck depression inventory. Data were analyzed with descriptive and analytical statistical (chip-square test) in SPSS software v.16. Conclusion: Depression was more frequent among ischemic heart disease patients than non-ischemic heart disease patients. According to the results, it seems to be appropriate to consider depression screening and psychiatric consulting among patients with ischemic heart diseases as a prevention tool. Keywords: Depression; Coronary Artery Disease; Myocardial Ischemia; Risk Factors